Las distintas tendencias geográficas - González González, María Jesús (Estudios humanísticos. Geografía, historia y arte, 2021)
This paper deals with the different geographical tendencies that have risen lately. The new technical statistic from the 50's onwards together with the influence of the social phenomena have given birth to a variety of new tendencies. The tradicional approach to Geography keeps away from these tendencies whose methods have been criticized.